Sequential biological removal of COD and ammonia-nitrogen from coke plant wastewater - Margaret Mukete Tonge; XU Xiang-yang; FENG Xiao-shan (浙江大学学报. 农业与生命科学版, 2000)
The feasibility and cost effectiveness of the novel anaerobic-anoxic-oxic (A-A-O) system for the treatment of coke plant wastewater was tested at laboratory scale. The system was investigated for its potential to reduce the chemical oxygen demand (COD), ammonia-nitrogen (NH3-N), thiocyanate (SCN-) and phenols. Treatability assessment studies were conducted for two distinct operational phases: phases Ⅰ and Ⅱ, respectively. The COD and NH3-N removal efficiencies during phase I depended on biotreatment alone. On the other hand, both biological treatment and powdered activated carbon treatment (PACT) were the removal factors during phase Ⅱ. The steady state COD and NH3-N removal efficiencies during phase Ⅰ and Ⅱ were 73% and 83% and 92.2% and 92.2%, respectively. phase Ⅱ therefore appeared to be more efficient as the COD removal efficiency was about 19% higher than that of phase Ⅰ.